Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

La noyante - Ouvrard, Hélène (Collection Littérature d'Amérique, 1980)
Ce roman pourrait être dédié aux gens qui ont encore "le courage de créer des traditions". L'auteure, comme l'écrit Madeleine Ouellette-Michalska, "articule la quête d'une liberté individuelle sur celle, plus vaste, d'un avenir collectif", en tentant une incursion dans la mythologie. Dans une antique demeure des bords du Richelieu, l'héroïne conjugue ses amours au féminin, et s'accepte Québécoise, c'est-à-dire divisée, avec "un oeil qui regrette l'Europe et l'autre qui convoite l'Amérique". Une oeuvre nationaliste et féministe. SDM.
Keywords: amériques; care; droits des femmes*; histoire et politique; nationalisme québécois; québec; roman; régions géographiques; thématiques; travail; travail domestique